Game Developer Readiness Index in Indonesia - Permana, Silvester Dian Handy (IJTB (International Journal of Technology And Business), 2018)
Indonesia is the fourth largest country in the world. The population has reached more than 260 million in 2017 and will increase by 1.49% annually. From the entire population there in Indonesia, 100 million People already enjoy internet services. The games apply the freemium method which means, players who spend some funds for their account will get more facilities than those who do not pay. 2.5 million People in Indonesia use their money to buy facilities in the game although the games played by them are mostly created by foreign countries. This is a new form of colonization in which we give some money to other countries. In response, Indonesia should be able to make their own games so that People here can become a technopreneur who gets revenue from it. People can make their own game developer company, a container for the games they are going to make. This research analyzes game developers in Indonesia level of readiness in making their own game. This research will involve a variety of new game developers in Indonesia. This research use questionnaire to get data from game developers. The researcher used modified E-Readiness Methodology from Hartman Sifonis in analyzing the level of readiness of game making in Jakarta. This methodology divides the analysis into 4 factors which are Leadership, Governance, Competencies, and Technology. This methodology was modified by adding marketing factors. The result from this research shows that the game making level of readiness in Indonesia is at the e-savvy level (3 from the scales of 5). This shows that People in Indonesia already have adequate infrastructure and technology but, not yet supported by government policy. Besides that, game developers ask to be given a guide to managing their company. The result of this analysis is used as a reference for the development of game making by the society in the future.